2001
DOI: 10.1081/ada-100104511
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Substance Use and Outcome in Combined Behavioral and Naltrexone Therapy for Opiate Dependence

Abstract: Intermittent use of nonopiate drugs is common during outpatient treatment for opiate dependence and may be a favorable prognostic indicator. This may support a "harm reduction" approach as opposed to a strict abstinence-oriented approach. Further research is needed to identify the optimal therapeutic stance toward other drug use during treatment for opiate dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
5
22
0
Order By: Relevance
“…Participants who smoked marijuana had less difficulty with sleep and anxiety and were more likely to remain in treatment as compared to those who were not using marijuana, regardless of whether they were taking dronabinol or placebo. This finding is consistent with our earlier reports showing the beneficial effects of moderate and intermittent marijuana use on compliance with naltrexone and opioid abstinence (Church et al, 2001; Raby et al, 2009). Although none of these studies used a controlled design to assess the effect of marijuana smoking a priori, the fact that we were able to replicate the finding in three separate studies strengthens its validity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Participants who smoked marijuana had less difficulty with sleep and anxiety and were more likely to remain in treatment as compared to those who were not using marijuana, regardless of whether they were taking dronabinol or placebo. This finding is consistent with our earlier reports showing the beneficial effects of moderate and intermittent marijuana use on compliance with naltrexone and opioid abstinence (Church et al, 2001; Raby et al, 2009). Although none of these studies used a controlled design to assess the effect of marijuana smoking a priori, the fact that we were able to replicate the finding in three separate studies strengthens its validity.…”
Section: Discussionsupporting
confidence: 94%
“…Observational data from several independent studies, and clinical experience, suggest that patients who use marijuana following induction onto naltrexone have better retention in treatment as compared to individuals who do not use marijuana (Church et al, 2001; Raby et al, 2009). This finding suggests marijuana may help alleviate withdrawal symptoms early in the course of naltrexone treatment and points to the role of the endocannabinoid system in preventing opioid dependence relapse.…”
Section: Introductionmentioning
confidence: 99%
“…There was, however, significantly better treatment retention among intermittent=moderate cannabis users compared to abstainers and heavy=consistent users. This is consistent with previous findings in a study of opiate dependence (6), which also suggested that moderate levels of cannabis use were associated with better outcome compared to minimal use or heavy use.…”
Section: Discussionsupporting
confidence: 92%
“…The literature on the impact of cannabis use on outcome of other substance dependencies is mixed. Some studies show a worsening of prognosis (3)(4)(5), while a few studies actually suggest no effect or favorable effects (6,7). Here, we report the impact of cannabis use during treatment on the outcome of cocaine dependent patients with ADHD.…”
Section: Introductionmentioning
confidence: 74%
“…Most research suggests that cannabis use, despite being frequent among MMT patients, is not associated with treatment outcomes (Budney, Bickel, & Amass, 1998;Church, Rothenberg, Sullivan, Bornstein, & Nunes, 2001;Epstein & Preston, 2003;Nava, Manzato, & Lucchini, 2007). One report even suggested that cannabis use was a favorable prognostic factor for treatment retention (Ellner, 1977).…”
Section: Introductionmentioning
confidence: 99%